ANALISIS PROSES PELAYANAN PENERBITAN SURAT KETERANGAN CATATAN KEPOLISIAN DI POLRES BUNGO - Putri Nurtria; Yasir Riady (Ensiklopedia of Journal, 2022)
This study aims to determine the quality of the Statemen of Good Conduct or SKCK issuance service process at the Bungo Police in the perspective of service quality theory according to Zeithaml et al. This study used a qualitative research method, with informants consisting of: (1) Head of Intelkam, Bungo Police; (2) three personnel from the Bungo Police Intelligence Unit; (3) eight people from the Bungo Regency who applied for the SKCK. The technique of determining informants using purposive sampling. Meanwhile, the data analysis technique uses qualitative analysis with data reduction, data presentation and drawing conclusions and verification. The results of this study indicate that the overall quality of the SKCK-making service process at the Bungo Police Intelligence and Security Unit office can be said to be quite good, but some deficiencies are still found, namely in the Assurance (Guarantee) dimension and the Empathy dimension. The supporting factors for the implementation of the SKCK issuance service process at the Bungo Resort Police are officers who support each other and encourage each other when providing SKCK-making services, then the Intelligence and Security Unit is also supported by assistive tools such as computers and other devices. While the inhibiting factors faced by the Bungo Police Intelligence Unit when processing SKCK issuance services were: there were limited officers who provided SKCK manufacturing services, only some officers were able to operate computer equipment, then the Bungo Police Intelligence Unit also did not have this filing cabinet to organize documents and archives.  archives so as not to be scattered on the service desk.